2010
DOI: 10.1007/s10725-010-9475-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of allelopathic response to low nitrogen and barnyardgrass competition in rice (Oryza sativa L.)

Abstract: To explore the molecular mechanism of allelopathic rice in response to low nitrogen (N) supply or accompanying weed stress, allelopathic rice PI 312777 and its counterpart Lemont were grown under low N supply or co-cultured with barnyardgrass [Echinochloa crus-galli (L.) Beauv.] in hydroponics. The suppression subtractive hybridization (SSH) technique was employed to isolate the up-regulated genes in the treated rice accession. The results indicated that the expression of the genes associated with N utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Low nitrogen supply suppressed the biosynthesis of protein, nucleic acid, and other metabolites, eventually resulting in low biomass and leaf area. Several studies have demonstrated that the nitrogen starvation-stress and low-nitrogen stress could induce genes expression in plants (Chen et al 2003;Fang et al 2010). The level of P5CS could also be regulated by the nitrogen supply Kishor et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Low nitrogen supply suppressed the biosynthesis of protein, nucleic acid, and other metabolites, eventually resulting in low biomass and leaf area. Several studies have demonstrated that the nitrogen starvation-stress and low-nitrogen stress could induce genes expression in plants (Chen et al 2003;Fang et al 2010). The level of P5CS could also be regulated by the nitrogen supply Kishor et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic acids are important in allelopathy and replanting disease incidence (Bais et al, 2004 ; Kulmatiski et al, 2008 ; Wu et al, 2015 ; Zhao et al, 2015 ). Phenolic compounds are autotoxins of the plants in monocropping system, such as Rehmannia glutinosa , cucumber, and tobacco (Fang et al, 2010 , 2013 ; Lin et al, 2010 ; Li et al, 2012 ; Zhou and Wu, 2012b ; Wu et al, 2015 ). Some studies indicate that phenolic acids change the soil microbial community with possible influences on plant performance (Zhou et al, 2012 , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the allelopathic rice accession PI responds more actively than the non-allelopathic rice accession LE to root exudates treatment. Previously reported morphological, physiological, and biochemical results indicated that PI is more sensitive than LE under various biotic and abiotic stresses (Shin et al 2000; He et al 2008; Fang et al 2010; Wang et al 2010; Kato-Noguchi 2011; He et al 2012). We suggest that this result derives from the genetic traits of the allelopathic rice accessions.…”
Section: Discussionmentioning
confidence: 97%
“…However, three decades after Dilday’s study, rice allelopathy has yet to be widely applied in practice. The main reason is that rice allelopathy is a quantitative trait that is heavily influenced by environmental conditions (Dilday et al 2000; Shin et al 2000; Fang et al 2010; Kato-Noguchi 2011; Wang et al 2010; He et al 2012). Rice allelopathic activity is polygenically controlled (Ebana et al 2001; Jensen et al 2001, 2008; He et al 2004; Junaedi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation